Cause-related marketing: an exploration of new avenues through conjoint analysis. Issue 6 (5th August 2019) - Kulshreshtha, Kushagra; Bajpai, Naval; Tripathi, Vikas; Sharma, Gunjan
Abstract : Purpose: Cause-related marketing (CrM) is one of the effective marketing concepts which draw high public exposure and make the cause and the organization known in the market. Further, it develops a higher inclination of the customers associating themselves with CrM-related campaigns. In this regard, CrM campaigns generally take hedonic products into consideration. The purpose of this paper (comprises two studies) is to: study 1, examine the attributes leading to successful CrM campaign and afterward when the results of Study 1 were found in line with the existing literature; and, Study 2, empirically examine the consumer preference for hedo-utilitarian products type in the CrM context. Design/methodology/approach: A total of 316 respondents participated in the survey. For selecting the appropriate research technique under the CrM study, the systematic review was conducted to arrive at a decision. Finally, conjoint analysis, a decompositional approach, was used for its ability to provide real-world setup to the respondents and keeping the social desirability bias at the minimum while assessing the consumer preference in the context of CrM. Findings: Much literature is available in favor of using hedonic products for successful CrM activities. However, none has conceptualized the hedo-utilitarian products that have an equally fair chance to succeed under CrM strategy. The present study confirmed the relevance of hedo-utilitarian products (utilitarian products having hedonic features) for attracting the consumers having cognitive and affective responses altogether. Practical implications: The novel concept of hedo-utilitarian product is introduced and empirically examined. The propositions and findings will facilitate the organizations in developing the products and marketing strategies in the context of CrM, giving them the option beyond the two product categories, i.e. hedonic and utilitarian. Accordingly, the companies may also focus and strategize for the "causmers, " i.e. the consumers who pay heed to the cause of the campaign during the purchase. Originality/value: While several of the dimensions in marketing have been explored, CrM is the least explored area in the Asian region. The attributes that may affect CrM were taken all together as another product feature/attribute under conjoint analysis exploring the attributes affecting CrM most, eventually, leading to higher consumer preference. Further, the concept of hedo-utilitarian products was introduced, empirically examined and recommended to future researchers for bringing it forward.